Infective Endocarditis Complicated by Large Aortic Pseudoaneurysm after Cardiac Surgery - Pelicano, NJ (2011)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2011-03-29T16:09:31Z No. of bitstreams: 1 Eur J Echocard 2006 394.pdf: 882682 bytes, checksum: 43653d522bc71449505f74642e213ba8 (MD5)